ChemInform Abstract: General Formation of Complex Tubular Nanostructures of Metal Oxides for the Oxygen Reduction Reaction and Lithium‐Ion Batteries. Issue 46 (24th October 2013) - Zhang, Genqiang; Xia, Bao Yu; Xiao, Chong; Yu, Le; Wang, Xin; Xie, Yi; Lou, Xiong Wen
Abstract Novel tube‐in‐tube nanostructures are synthesized for many binary and ternary metal oxides, including CuCo2O4, ZnCo2O4, CoMn2O4, ZnMn2O4, MnCo2O4, NiCo2O4, Mn2O3, Co3O4, NiO, and Fe2O3 by thermal annealing (380—450 °C, 4 h) of precursors obtained from carbon nanofibers dispersed in ethylene glycol with different metal acetates (reflux for 2 h).